2004
DOI: 10.1002/humu.10284
|View full text |Cite
|
Sign up to set email alerts
|

Knobloch syndrome: Novel mutations inCOL18A1, evidence for genetic heterogeneity, and a functionally impaired polymorphism in endostatin

Abstract: Knobloch syndrome (KNO) is an autosomal recessive disorder characterized by high myopia, vitreoretinal degeneration with retinal detachment, and congenital encephalocele. Pathogenic mutations in the COL18A1 gene on 21q22.3 were recently identified in KNO families. Analysis of two unrelated KNO families from Hungary and New Zealand allowed us to confirm the involvement of COL18A1 in the pathogenesis of KNO and to demonstrate the existence of genetic heterogeneity. Two COL18A1 mutations were identified in the Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 34 publications
5
83
0
1
Order By: Relevance
“…Survival analysis based on Col181/ES carrier status after adjusting for demographics variables or hemodynamic variables linked a genetic variation in this gene to risk of death in PAH ( Figure 5A). Thus, carriers of ES variant N104ES, which impairs receptor binding (27) and is associated with decreased serum ES in our analysis, had improved survival even after adjusting for invasive cardiopulmonary markers of disease severity, implicating the Col18a1 gene product as a heritable determinant of mortality in PAH.…”
Section: Col18a1 Variant and Pah Outcomesmentioning
confidence: 65%
“…Survival analysis based on Col181/ES carrier status after adjusting for demographics variables or hemodynamic variables linked a genetic variation in this gene to risk of death in PAH ( Figure 5A). Thus, carriers of ES variant N104ES, which impairs receptor binding (27) and is associated with decreased serum ES in our analysis, had improved survival even after adjusting for invasive cardiopulmonary markers of disease severity, implicating the Col18a1 gene product as a heritable determinant of mortality in PAH.…”
Section: Col18a1 Variant and Pah Outcomesmentioning
confidence: 65%
“…This hypothesis is supported by the fact that collagen XVIII is a heparan-sulfate proteoglycan that is expressed in the chicken retina [54] as well as in the mammalian retina and fetal brain [24]. Furthermore, mutations in the col 18a1 gene in mammals are responsible for the Knobloch syndrome, an autosomal recessive disorder, which is characterized by myopia, vitreoretinal degeneration, and occipital encephalocele [22][23][24], and similar defects are found in the drCol 15a1b morphants. These findings represent further evidence of the complex evolution and functional divergence of gene families and of the conserved common regulatory functions that, in this case, might be involved in harnessing adult stem cell biology.…”
Section: Discussionmentioning
confidence: 91%
“…Both genes are expressed in a wide range of different tissues [15,21]; while mammalian col 15a1 seems to be more closely associated with muscle cells and microvessels, mammalian col 18a1 seems to be involved in eye development. Indeed, mutations in the human col 18a1 gene are associated to the Knobloch syndrome [22][23][24]. In turn, studies with col 15a1 knockout mice have revealed that this collagen is involved in the stabilization of the basal laminae from muscular and endothelial cells [25].…”
Section: Introductionmentioning
confidence: 99%
“…It can be caused by COL18A1 mutations resulting in truncation or loss of protein due to nonsense mediated decay (Sertie et al 2000;Suzuki et al 2002) but is genetically heterogeneous as additional loci have been identified (Khaliq et al 2007;Menzel et al 2004). This genetic heterogeneity combined with genetic modifiers (Utriainen et al 2004) may underlie the highly variable clinical presentation of Knobloch syndrome.…”
Section: Knobloch Syndromementioning
confidence: 99%